PENGARUH PENGARUH KOMUNIKASI PEMASARAN TERHADAP EKUITAS MEREK PADA PT. BINA KARYA PRIMA - YULIA NASUTION; BAMBANG SUTEJO (LP2MTBM MAKARIOZ, 2022)
Bina Karya Prima Tbk is a company that develops its business by producing daily necessities, such as soap and beauty products, etc. One of the whitening soap products from PT. BKP is Shinzui. Shinzui soap product is a skin whitening product to become a dazzling bright white which is the dream of most Indonesian women. The charm of beauty from within will be radiated to the maximum with dazzling bright white skin. Therefore, it takes the right skin whitening soap for a good skin whitening soap. Shinzui Bar Soap Matsu is brought to you by Shinzui for white Indonesian women. The purpose of this study was to determine the effect of advertising, sales promotion and publicity on brand equity either partially or simultaneously at PT. Prima Karya Development. The total population in this study were 75 customers and the sample was 75 customers using the saturated sample method. The test used is multiple linear regression and hypothesis testing. The results of this study indicate that advertising has a significant effect on brand equity of PT. Prima Karya Development. Sales promotion has a significant effect on brand equity of PT. Prima Karya Development. Publicity has no significant effect on brand equity of PT. Prima Karya Development. Simultaneously the variables of advertising, sales promotion and publicity have a significant effect on brand equity of PT. Prima Karya Development.